A Simple Spectrophotometric Method for the Determination of Clarithromycin from Pharmaceutical Preparation. - ARBAD, B.R.; JADHAV, S.M. (Asian Journal of Chemistry, 2010)
A spectroscopic method is developed for the estimation of clarithromycin in its dosage forms using 0.02 M solution (w/v) of 2-nitrobenzaldehyde in glacial acetic acid in presence of hydrochloric acid. 2-Nitrobenzaldehyde reagent forms a reddish pink coloured complex with the drug, which has an absorption maximum at 486 nm. The colour, so produced, is stable perfectly for about 30 min. Both drugs obey the Lambert-Beer's law in the concentration range employed for this method. The results of analysis have been validated statistically and by recovery study. The proposed method is simple, selective, rapid and economical for the determination of clarithromycin.